B5 High-volume PCEA versus PIEB for labour analgesia: a randomised, double-blind, two-center, non-inferiority study in nulliparous women investigating quality of pain relief. (11th August 2022) - Filetici, N; Roofthooft, E; Rex, S; Wong, CA; Van de Velde, M
Abstract : Background and Aims: Maintenance of neuraxial labour analgesia using programmed intermittent epidural boluses (PIEB) is superior compared to continuous epidural infusions with/without patient controlled epidural analgesia (PCEA), causing less breakthrough pain, motor block and local anesthetic (LA) consumption 1 . Compared to low-volume PCEA without background infusion, PIEB produces less breakthrough pain and motor block, despite higher LA consumption. The goal of this randomised, double-blind, non-inferiority study was to investigate if high-volume PCEA without background infusion compared to PIEB+PCEA, set with equal boluses, results in a similar incidence of breakthrough pain and LA consumption. Methods: Following ethics approval and written consent, combined spinal-epidural for labour was performed in 360 nulliparous women. Analgesia was maintained with ropivacaine 0.12% and sufentanil 0.75mcg/mL. Patients randomly received high-volume PCEA without background infusion set at 10 mL bolus with a 30 min lock-out or PIEB as 10 mL bolus every hour plus PCEA boluses of 5 mL with a 30 min lock-out. Breakthrough pain, motor block and LA consumption were recorded. Results: Final analysis was performed in 336 women (PCEA n=170; PIEB-PCEA n=166). Breakthrough pain occurred in 11.2% in the PCEA-group and 10.8% in the PIEB-group. Total LA consumption was lower in the PCEA-group than in the PIEB-group (mean 53.1 versus 65.2 mL respectively, p< 0.0001). Motor block was not different between groups (p=0.783). Conclusions: High-volume PCEA without background infusion and PIEB showed a similar incidence of breakthrough pain and motor block. The PCEA-group had a lower total LA consumption.